2006
DOI: 10.1203/01.pdr.0000203092.83074.eb
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic Isolated Human Glycerol Kinase Deficiency Associated with Splice-Site Mutations and Nonsense-Mediated Decay of Mutant RNA

Abstract: Isolated glycerol kinase deficiency (GKD) is an Xlinked inborn error of metabolism that is either symptomatic or asymptomatic. GKD is due to deletions of, or mutations within, the GK gene, and there is no genotype-phenotype correlation. We identified three patients with asymptomatic GKD, determined that they had GK splice-site mutations, and studied the stability of their GK mRNA to understand the molecular mechanism of the GKD. All three patient mutations caused a frameshift and introduction of a premature st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 14 publications
0
6
1
Order By: Relevance
“…Third, it may be related to Nonsense Mediated Decay (NMD). Zhang et al, found that aberrant mRNA generated by splice site mutations of the GK gene can be eliminated by NMD in the asymptomatic form of GKD [9]. In contrary, there was no NMD in our study, and reviewed the other split-site mutations previously reported, no NMD was found too [4,5].…”
contrasting
confidence: 63%
See 1 more Smart Citation
“…Third, it may be related to Nonsense Mediated Decay (NMD). Zhang et al, found that aberrant mRNA generated by splice site mutations of the GK gene can be eliminated by NMD in the asymptomatic form of GKD [9]. In contrary, there was no NMD in our study, and reviewed the other split-site mutations previously reported, no NMD was found too [4,5].…”
contrasting
confidence: 63%
“…Interestingly, most of the patients with split-site mutation reported previously presented with asymptomatic form of GKD [4,5,[7][8][9]. Only one patient from the literature (IVS9-1G>T) who had a history of metabolic and CNS crises at the age 6 years and 3 months, indicating the symptomatic form of GKD, but he was uneventful in the neonatal period and early childhood [10].…”
Section: Citation: Zeng L Mei L Tan H Li H Lv W Et Al (2017) a mentioning
confidence: 99%
“…The 15 studies included a total of 39 adult participants (aged 23-70 years). All articles reported severe HTG: thirteen articles showed a range of TG from 484 to 1992 mg/dL [5,7,8,[14][15][16][17][18][19][20][21][22][23], however two of them did not report concrete values of TG [24,25]. Twelve articles reported high levels of plasma glycerol [5,7,8,14,15,[17][18][19][20][21][22][23][24], with a range from 0.195 to 210 mmol/L, and eight of them showed the presence of glycerol in urine.…”
Section: Participants and Main Study Characteristicsmentioning
confidence: 99%
“…p. (Asn288Asp), p.(Ala305Val), p.(Gln438Arg), p.(Thr96Ile) p.(Cys358Tyr), p.(Gly280Ala) [5,20,21,24]; c) three articles [20,22,25] reported four causative splice site mutation:…”
Section: Participants and Main Study Characteristicsmentioning
confidence: 99%
“…In GK deficiency, variation in protein stability and RNA processing appear to modify phenotype. 10 The genetic underpinnings of Mendelian disease will continue to integrate with theoretical and experimental work in biochemistry to explicate phenotypic complexity, for example, by providing a better understanding of the kinetic behavior of enzyme reactions and metabolic flux, which behave as nonlinear systems. 11 However, the precise phenotypic outcomes will probably remain predictable only at low resolution because ''for many diseases, only a subset of all mutations reliably predicts phenotypes.''…”
Section: Introductionmentioning
confidence: 99%